2008
DOI: 10.1038/jid.2008.156
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E6/E7 Oncogenes Promote Mouse Ear Regeneration by Increasing the Rate of Wound Re-epithelization and Epidermal Growth

Abstract: Mammals have limited regeneration capacity. We report here that, in transgenic mice (Tg(bK6-E6/E7)), the expression of the E6/E7 oncogenes of human papilloma virus type 16 (HPV16) under the control of the bovine keratin 6 promoter markedly improves the mouse's capacity to repair portions of the ear after being wounded. Increased repair capacity correlates with an increased number of epidermal proliferating cells. In concordance with the expected effects of the E6 and E7 oncogenes, levels of p53 decreased and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
2
14
0
2
Order By: Relevance
“…A few studies of wound-healing events have shown that many drugs can promote wound healing by accelerated re-epithelialization through enhanced keratinocyte migration and proliferation. [20][21][22][23] In our study, we initially focused on keratinocytes to investigate the morphological changes mediated by AgNPs. In agreement with the results of others, our histological findings demonstrate that AgNPs do indeed promote the proliferation and migration of keratinocytes from wound edge toward the wound center.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies of wound-healing events have shown that many drugs can promote wound healing by accelerated re-epithelialization through enhanced keratinocyte migration and proliferation. [20][21][22][23] In our study, we initially focused on keratinocytes to investigate the morphological changes mediated by AgNPs. In agreement with the results of others, our histological findings demonstrate that AgNPs do indeed promote the proliferation and migration of keratinocytes from wound edge toward the wound center.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial re-epithelization, epidermal cell migration from the intact surrounding tissue appears to be a major contributor to the growing epidermis, especially in the repairing tissue of transgenic mice. We also found that there is a significantly higher number of putative epidermal stem cells in Tg(bK6-E6/E7) than in wild-type mice (Valencia et al 2008).…”
Section: Introductionmentioning
confidence: 87%
“…The construction of transgenic mice containing the HPV16 E6/E7 viral oncogenes under the promoter of the bovine keratin 6 gene (Tg[bK6-E6/E7] mice), their propagation, the expression of the viral oncogenes and the skin phenotype was already described (Escalante-Alcalde et al 2000;Valencia et al 2008). Mice were housed and treated according to the American Association of Laboratory Animal Care (AALAC) regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23,69] In low-risk HPV types, the wound healing process may hold an important role in the initial proliferation of the infected cells. [70] For the highrisk HPV types, viral proteins E6 and E7 function in the cell proliferation in the basal and parabasal cell layers. This function is particularly important at cervical sites where neoplasias may occur.…”
Section: Role Of Hpv In Cancer Developmentmentioning
confidence: 99%